Spring Ephemerals Adapt to Extremely High Light Conditions via an Unusual Stabilization of Photosystem II - Tu, Wenfeng; Li, Yang; Liu, Wu; Wu, Lishuan; Xie, Xiaoyan; Zhang, Yuanming; Wilhelm, Christian; Yang, Chunhong (Frontiers in Plant Science, 2016)
Ephemerals, widely distributed in the Gobi desert, have developed significant characteristics to sustain high photosynthetic efficiency under high light (HL) conditions. Since the light reaction is the basis for photosynthetic conversion of solar energy to chemical energy, the photosynthetic performances in thylakoid membrane of the spring ephemerals in response to HL were studied. Three plant species, namely two C3 spring ephemeral species of Cruciferae: Arabidopsis pumila (A. pumila) and Sisymbrium altissimum (S. altissimum), and the model plant Arabidopsis thaliana (A. thaliana) were chosen for the study. The ephemeral A. pumila, which is genetically close to A. thaliana and ecologically in the same habitat as S. altissimum, was used to avoid complications arising from the superficial differences resulted from comparing plants from two extremely contrasting ecological groups. The findings manifested that the ephemerals showed significantly enhanced activities of photosystem (PS) II under HL conditions, while the activities of PSII in A. thaliana were markedly decreased under the same conditions. Detailed analyses of the electron transport processes revealed that the increased plastoquinone pool oxidization, together with the enhanced PSI activities, ensured a lowered excitation pressure to PSII of both ephemerals, and thus facilitated the photosynthetic control to avoid photodamage to PSII. The analysis of the reaction centers of the PSs, both in terms of D1 protein turnover kinetics and the long-term adaptation, revealed that the unusually stable PSs structure provided the basis for the ephemerals to carry out high photosynthetic performances. It is proposed that the characteristic photosynthetic performances of ephemerals were resulted from effects of the long-term adaptation to the harsh environments.